Persepsi Konsumen Terhadap Kualitas Produk Organik Tanaman Hortikultura di Kebun Praktek Fakultas Pertanian Universitas Nusa Nipa Maumere - Yosefina Jelita Numbar; Sarlina Noni (Peneliti.net, 2021)
Organic food is food that is produced little or completely free from chemical elements in the form of fertilizers, pesticides, hormones, and drugs. Perception is the experience of learning about agriculture or the relationships obtained by inferring information and interpreting messages. Therefore, marketers must pay attention to the needs and tastes of consumers in order to face competition. The formulation of the problem in this study is how consumers' perceptions of the quality of organic horticultural plant products. The purpose of this study was to determine consumer perceptions of the quality of organic horticultural products in the Garden of Practice, Faculty of Agriculture, University of Nusa Nipa Maumere. This research is a quantitative study with 30 respondents using data collection techniques in the form of a questionnaire. The data analysis used in this research is quantitative analysis and simple linear regression analysis. This research was conducted at the Practice Garden of the Faculty of Agriculture, University of Nusa Nipa Maumere for 2 months, from 01 October to 04 December 2020. The results of this study indicate that there is no significant influence between consumer perceptions and the quality of organic products in the Garden of the Faculty of Agriculture, University of Nusa Nipa Maumere. And there is a significant influence between consumer perceptions and the quality of organic products in the Garden of the Faculty of Agriculture, University of Nusa Nipa Maumere.